JURIDICAL REVIEW OF THE ACQUISITION OF SHARES OF A LIMITED LIABILITY COMPANY IN A BUSINESS LAW PERSPECTIVE - Cahyani, Gisella Tiara; Azzahra, Najwa Maulida; Hosnah, Asmal ul (Syiar Hukum, 2023)
Acquisition of shares in a business often occurs when one company buys shares of another company. This article discusses the juridical aspects of share acquisition in the context of a Limited Liability Company (PT) by analyzing legal regulations, the rights and obligations of parties, and the legal protection of shareholders. As well as the legal impacts that may arise as a result of the transaction, by reviewing legal issues that may arise in the acquisition of shares, such as unfair business competition, legal protection of shareholders. Through this understanding, this article aims to provide a deeper understanding of the legal regulations governing share acquisition in the context of limited liability companies by explaining their implications in the business environment.